USE OF DESFLURANE: CONSIDERATIONS AND CONTROVERSIES - Ognjanovska Simjanovska, Violeta; Shirgoska, Biljana; Naumovski, Filip (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Desflurane stands as a pivotal volatile anesthetic in contemporary anesthesia practice and has been a cornerstone of modern anesthesia practice due to its rapid onset and offset of action. Despite its clinical advantages, the environmental footprint of desflurane, characterized by significant greenhouse gas emissions, has sparked a debate on its continued use and potential regulatory measures. This article evaluates desflurane’s clinical benefits, alongside its environmental implications, offering insights into possible regulation perspectives. Highlighting its favorable pharmacokinetic properties, rapid induction, hemodynamic stability and bronchodilator effects, against its contribution to climate change, the study aims to foster a balanced discourse on desflurane’s role in healthcare, advocating for a harmonization of clinical needs with ecological stewardship.